2011
DOI: 10.1063/1.3609078
|View full text |Cite
|
Sign up to set email alerts
|

In-situ magnetic nano-patterning of Fe films grown on Cu(100)

Abstract: Metastable paramagnetic face-centered cubic (fcc) Fe films grown on a Cu(100) single crystal at room temperature can be transformed to the ferromagnetic body-centered cubic (bcc) structure by ion irradiation. We have employed this technique to write small ferromagnetic patches by Ar þ irradiation through a gold coated SiN mask with regularly arranged 80-nm diameter holes, which was placed on top of the as-prepared fcc Fe films. Nanopatterning was performed on both 8-monolayer (ML) Fe films grown in ultrahigh v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…patterning) to reduce dimension and allow device miniaturization and densification. However, nanopatterning of magnetic materials and, in particular, films is a challenge as they are not readily or simply etched and films grown on silicon tend to suffer damage and delamination during conventional processing6. The magnetics used tend to be complex mixtures and can suffer composition changes during processing7.…”
mentioning
confidence: 99%
“…patterning) to reduce dimension and allow device miniaturization and densification. However, nanopatterning of magnetic materials and, in particular, films is a challenge as they are not readily or simply etched and films grown on silicon tend to suffer damage and delamination during conventional processing6. The magnetics used tend to be complex mixtures and can suffer composition changes during processing7.…”
mentioning
confidence: 99%
“…We have shown that it is possible to grow metastable, epitaxial fcc Fe78Ni22 on H-Si(100) with a Cu(100) buffer layer, and that using a focused ion beam, we can create magnetic micro-and nanostructures with tuneable magnetization. The lower size limit of such nanostructures is given by the focus of the ion beam and the size of the bcc nuclei [5]. The magnetic properties of the films are comparable to the properties of Fe78Ni22 films prepared on Cu(100) single crystal substrates [11].…”
Section: Resultsmentioning
confidence: 87%
“…The metastable Fe/Cu(100) spontaneously transforms to bcc phase at 10 ML [8], but this limit can be shifted to 22 ML by dosing CO [9] and even further by alloying Fe with 22% of Ni [10]. We have shown that it is possible to fabricate magnetic nanostructures in these films by ion-beam irradiation using proximity masks [5] or focused ion beams (FIB) and that by suitably chosen FIB patterning procedures it is possible to tune saturation magnetization and also the magnetic anisotropy of the transformed structures [11].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…First and presumably the major contribution increasing the width of the waveguide is the finite size and shape of the focused ion beam spot. Furthermore, in our previous work [30] it was shown that the bcc crystallites protrude to the fcc phase slightly further from the ion impact spot and thus they again effectively increase the width of the waveguides (the protrusion length is approx. 50 nm).…”
mentioning
confidence: 95%